2020
DOI: 10.1039/d0cp04454g
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalysed methoxycarbonylation of ethene with bidentate diphosphine ligands: a density functional theory study

Abstract: Catalytic methoxycarbonylation of ethene with a bidentate tertiary phosphine (DTBPX) and palladium has been explored at the B3PW91-D3/PCM level of density functional theory. Three different pathways for formation of methyl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…Here we have added an example of the possible mechanistic pathways from our recent work on methoxycarbonylation of ethene. 98 The alkoxy cycle begins with the migratory insertion of CO to the Pd-OMe bond followed by insertion of alkene into the ester functionality with alcoholysis as the final step (Scheme 3A). The hydride cycle operates via a Pd-H complex, which begins with an a,b alkene insertion, followed by an a,a insertion of the alkyl group into coordinated CO closing at the alcoholysis step (Scheme 3B).…”
Section: Computational Mechanistic Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we have added an example of the possible mechanistic pathways from our recent work on methoxycarbonylation of ethene. 98 The alkoxy cycle begins with the migratory insertion of CO to the Pd-OMe bond followed by insertion of alkene into the ester functionality with alcoholysis as the final step (Scheme 3A). The hydride cycle operates via a Pd-H complex, which begins with an a,b alkene insertion, followed by an a,a insertion of the alkyl group into coordinated CO closing at the alcoholysis step (Scheme 3B).…”
Section: Computational Mechanistic Studiesmentioning
confidence: 99%
“…Their methanolysis barriers with similar schemes turned to be much lower than those we recently published for a different system. 98 These low barriers come from further destabilisation of the Pd-acyl complex due to greater steric bulk on the phosphines; however, off-cycle intermediates appeared to be the MARIs. In this study the MHP scheme 87 was found to be crucial to account for the extent of reversibility of individual reaction steps, in order to account for the observations from deuterium labelling studies.…”
Section: Computational Mechanistic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we have even more confidence that the ligands described in this paper are worthy of much deeper investigation, as are the new ligands under development within our group. A recent DFT study may help advance the mechanistic insights of this process [78]. Further synthetic details of in situ methods for phosphane preparation can be found in the Supplementary Materials.…”
Section: Catalyst Testing: Initial Evaluation Of Ferrocene-based Ligands Vs Alpha Ligand In the Palladium-catalysed Formation Of Methyl Pmentioning
confidence: 99%